Juridical Analysis of Over Credit in Motor Vehicle Credit Agreement with Fiduciary Guarantee in View of Undang-Undang Nomor 42 of 1999 on Fiduciary Guarantee - Puspawangi Prameswari; Temmy Fitriah Alfiany (Journal of Law, Politic and Humanities, 2024)
In the world of motor vehicle credit financing as stipulated in Pasal 23 ayat 2 of Undang-Undang Nomor 42 Tahun 1999 concerning Fiduciary which explains that a debtor is prohibited from selling transferring and or mortgaging the object of fiduciary guarantee, except with the permission of the creditor, but in reality the practice of transferring (Over Credit) or mortgaging often occurs among the public as in case study Number. 130/PID SUS/2023/PN SKB. This research examines and analyzes related to over credit that occurs without the knowledge of creditors that occurs among the community, therefore researchers raise two problem formulations among them. First, the legal consequences to the creditor arising from the decision in case No. 130/pid sus/2023/pn skb. 130/PID SUS/2023/PN SKB. Second, the legal consequences for debtors who over credit without the knowledge of the creditor. This research uses an analytical descriptive method with a normative juridical approach, in which data and information are analyzed normatively. The results showed that it is important to be careful in determining a person who can be held legally responsible, because those who can be held legally responsible are legal subjects who carry out legal relations in this study are creditors and debtors.